Scar endometriosis: not a rarity now a day - Mangla, Mishu; Nautiyal, Ruchira; Deepmala, Deepmala; Chhatwal, Jashan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Endometriosis at the site of previous surgery scar is much on the rise now-a-days mainly due to increased rate of caesarean sections. Generally, it presents as a triad of underlying mass at the incision site, cyclical menstrual scar pain with or without discharge from scar site, and history of previous gynecological or obstetric surgery leads to the preoperative diagnosis. In rare cases, the clinical presentation is atypical, and diagnosis is mad after surgical excision. Here we discuss a case of scar endometriosis that presented to us with complaint of greenish coloured discharge from a lesion below the primary scar site 5 years after the primary surgery. Through this article, authors wish to discuss the etiology, management and preventive measures for scar endometriosis.